Data and code for "To every rule there is an exception: A rational extension of Loewenstein's rule" - Fant, Magnus; Ångqvist, Mattias; Hellman, Anders; Erhart, Paul (Chalmers University of Technology, 2020)
This data set contains data and code related to the paper "To every rule there is an exception: A rational extension of Loewenstein’s rule".
Keywords: Physical Sciences; Fysik